Development of a radiolabeled site-specific single-domain antibody positron emission tomography probe for monitoring PD-L1 expression in cancer - Yinfei Chen; Shiyu Zhu; Jiayu Fu; Jianguo Lin; Yan Sun; Gaochao Lv; Minhao Xie; Tao Xu; Ling Qiu (Elsevier, 2022)
Despite advances in immunotherapy for the treatment of cancers, not all patients can benefit from programmed cell death ligand 1 (PD-L1) immune checkpoint blockade therapy. Anti-PD-L1 therapeutic effects reportedly correlate with the PD-L1 expression level; hence, accurate detection of PD-L1 expression can guide immunotherapy to achieve better therapeutic effects. Therefore, based on the high affinity antibody Nb109, a new site-specifically radiolabeled tracer, 68Ga-NODA-cysteine, aspartic acid, and valine (CDV)-Nb109, was designed and synthesized to accurately monitor PD-L1 expression. The tracer 68Ga-NODA-CDV-Nb109 was obtained using a site-specific conjugation strategy with a radiochemical yield of about 95% and radiochemical purity of 97%. It showed high affinity for PD-L1 with a dissociation constant of 12.34 ± 1.65 nM. Both the cell uptake assay and positron emission tomography (PET) imaging revealed higher tracer uptake in PD-L1-positive A375-hPD-L1 and U87 tumor cells than in PD-L1-negative A375 tumor cells. Meanwhile, dynamic PET imaging of a NCI-H1299 xenograft indicated that doxorubicin could upregulate PD-L1 expression, allowing timely interventional immunotherapy. In conclusion, this tracer could sensitively and dynamically monitor changes in PD-L1 expression levels in different cancers and help screen patients who can benefit from anti-PD-L1 immunotherapy.